Religions of the Constantinian Empire - Edwards, Mark (Oxford University Press, 2015)
Religions of the Constantinian empire' provides a synoptic review of Constantine's relation to all the cultic and theological traditions of the Empire during the period from his seizure of power in the west in 306 CE to the end of his reign as autocrat of both east and west in 337 CE. Divided into three parts, the first considers the efforts of Christians to construct their own philosophy, and their own patterns of the philosophic life, in opposition to Platonism. The second assembles evidence of survival, variation or decay in religious practices which were never compulsory under Roman law. The 'religious plurality' of the second section includes those cults which are represented as demonic burlesques of the sacraments by Firmicus Maternus. The third reviews the changes, both within the church and in the public sphere, which were undeniably prompted by the accession of a Christian monarch. In this section on 'Christian polyphony', Mark Edwards expertly moves on from this deliberate petrifaction of Judaism to the profound shift in relations between the church and the civic cult that followed the Emperor's choice of a new divine protector